(untitled) (Jurnal Manajemen dan Organisasi, 2016)
PT Indofood CBP Sukses Makmur Branch Bandung Noodle Division is a company that realizes the importance of work culture and commitment. It is proven by the work culture that the company have implemented in order to guarantee better quality work result, and increase the satisfaction of employees’ work.The objectives of this study are 1) identifying the work culture at PT. Indofood CBP Sukses Makmur Branch Bandung Noodle Division; 2) identifying work commitments on PT. Indofood CBP Sukses Makmur Branch Bandung Noodle Division; and 3) analyzing the influence of work culture with respect to the commitment of employees in PT Indofood CBP Sukses Makmur Branch Bandung Noodle Division. This research shows that Noodle Divsion of the company in Bandung applies excellent work culture and the employees commit. The work culture that is based on excellent, discipline, integrity, innovative, and respect gives positive and significant impacts on employees’ commitment, while unity doesn’t give significant impact on employees’ commitment. Keyword: work culture, employee commitment, PT Indofood CBP Prosperous Successes Tbk Bandung branch division of the noodle